EVALUASI PEMELIHARAAN JARINGAN IRIGASI WONOTORO TAHUN 2019 SAMPAI 2021 - Rahmadi, Wahyu; Solikin, Mochamad; Jumadi, Jumadi; Pudyastuti, Purwanti Sri; Harnaeni, Senja Rum (Politeknik Negeri Semarang, 2024)
Evaluation or irrigation network maintenance is needed to determine and function of irrigation network after maintenance. One of the irrigation networks whose maintenance needs to be evaluated is the Wonotoro irrigation network. The irrigation network receives continuous maintenance every year, both routine and periodic maintenance. This study aims to evaluate the physical condition of the wonotoro irrigation network in 2019 to 2021, analyze trends in the condition of the network after maintenance from 2019 to 2021 and measure the efficiency of irrigation water distribution in 2021, in this study using a quantitative descriptive method. The results showed that in 2019 the condition was 80.02% of the classification slighty damaged, in 2020 the condition was 79.14% of the classification moderately damaged and in 2021 the condition was 77.80% of the classification moderately damaged. The trend of the physical condition of the Wonotoro irrigation network has decreased every year. The decline in conditions from 2019 to 2020 was 0,88% while from 2020 to 2021 it had decreased by 1,33%. Measurement of the efficiency of irrigation water distribution in 2021 is 49.39%.